The Effect of Discovery Learning Model to Improve Learning Outcomes and Chemical Process Skills - Simanjuntak, Hendra; Silalahi, Hasian P.K.A (Jurnal Basicedu, 2022)
The purpose of this research is to improve learning outcomes and chemical process skills through the Discovery Learning learning model on the reaction rate material. This research was conducted at SMA Negeri 3 Pematangsiantar in class XI MIA 2 with 29 students as the subject. This type of research is classroom action research which consists of planning, implementing actions, observing and reflecting using the Discovery Learning learning model. The test is used to measure the learning outcomes of students' initial abilities and learning outcomes, and the observation sheet is used to measure chemical process skills. Learning using the Discovery Learning model is proven to be effective in improving student learning outcomes and chemical process skills. The value achieved is still categorized in the Very Good criteria. Based on the analysis of chemical process skills, the success of the application in improving students' science process skills was 82.57% at the second meeting of the first cycle and increased again by 90.5% at the second meeting of the second cycle. The conclusion of this study is that the application of learning using the Discovery Learning model has proven to be effective in improving student learning outcomes and science process skills of SMA Negeri 3 Pematangsiantar students in class XI MIA 2.